Phase coherent excitation of SABRE permits simultaneous hyperpolarization of multiple targets at high magnetic field. Issue 12 (10th March 2022) - Lindale, Jacob R.; Eriksson, Shannon L.; Warren, Warren S.
Abstract : New excitation strategies allow generation of hyperpolarization on multiple targets directly in a conventional NMR spectrometer. Abstract : Hyperpolarization methods in magnetic resonance overcome sensitivity limitations, especially for low-γ nuclei such as 13 C and 15 N. Signal Amplification By Reversible Exchange (SABRE) and extended SABRE (X-SABRE) are efficient and low-cost methods for generating large polarizations on a variety of nuclei, but they most commonly use low magnetic fields (μT–mT). High field approaches, where hyperpolarization is generated directly in the spectrometer, are potentially much more convenient but have been limited to selectively hyperpolarize single targets. Here we introduce a new pulse sequence-based approach that affords broadband excitation of SABRE hyperpolarization at high magnetic fields without having to tailor pulse sequence parameters to specific targets. This permits simultaneous hyperpolarization of multiple targets for the first time at high field and offers a direct approach to integration of high-field SABRE hyperpolarization into routine NMR applications, such as NMR-based metabonomics and biomolecular NMR.